Going social: Success in online recruitment of men who have sex with men for prevention HIV vaccine research. Issue 27 (14th June 2017) - Buckingham, Lindsey; Becher, Julie; Voytek, Chelsea D.; Fiore, Danielle; Dunbar, Debora; Davis-Vogel, Annet; Metzger, David S.; Frank, Ian
Abstract: Objective: To compare the use of four different social media sites to recruit men who have sex with men (MSM) and transgender women to a phase 2b HIV prevention vaccine trial, HVTN 505. Design: Retrospective, observational study. Methods: The University of Pennsylvania HIV Vaccine Trials Unit (Penn HVTU) employed street outreach and online recruitment methods to recruit participants for HVTN 505 using a combination of national recruitment images/messages with Philadelphia-specific language and imagery. We compared the efficiency (number of enrolled participants per number of completed phone screens) and effectiveness (number of enrolled participants per time interval employed) of each strategy, as well as the demographics and risk behaviors of the populations. Results: Online recruitment strategies populated 37% (71/191) of trial participants at our site. Among the four social media strategies employed, 45.1% (32/71) were enrolled through Facebook, 16.9% (12/71) through Craigslist, 15.5% (11/71) through a web-based marketing company (WBMC), and 22.5% (16/71) via GRINDR. The number of participants enrolled per month of strategy and the months the strategy was employed were Facebook - 32(33 months), Craigslist - 12(33 months), WBMC - 11(6 months), and GRINDR - 16(0.56 months). In-person and online recruitment strategies yielded participants of similar demographics and levels of risk behavior. Conclusion: Use of several social media recruitment modalities produced large numbers of MSM engaging in high risk behavior and willing to participate in an HIV prevention vaccine trial. In comparison to other social media and online strategies, recruitment via GRINDR was the most effective.